Behavioral Monitoring Systems in Complex Organizations - Gannon, Martin J. (Academy of Management Review, 1977)
In this article the author examines the use of questionnaire surveys in order to develop vast information data-bases called behavioral monitoring systems. He compares these systems with other questionnaire approaches in terms of size, type of survey and purpose of survey. The survey types he discusses are single and repeated. Single surveys are used to determine cause of problems while repeated surveys allow researchers to chart changes over time. Survey purposes fall into two categories as well, the testing of hypotheses and the diagnosis of organizational problems. He discusses how these systems provide organizations will vital data about themselves that can serve to improve an organizations' overall function.